What Is the Best Method to Achieve Safe and Precise Stent-Graft Deployment in Patients Undergoing TEVAR? - Gottardi, Roman; Berger, Tim; Voetsch, Andreas; Winkler, Andreas; Krombholz-Reindl, Philipp; Farkouh, Andre; Kondov, Stoyan; Rylski, Bartosz; Sodian, Ralf; Czerny, Martin (The Thoracic and Cardiovascular Surgeon, 2020)
Thoracic endovascular aortic repair (TEVAR) for aortic pathologies requires sufficient landing zone of ideally more than 25 mm for safe anchoring of the stent-graft and prevention of endoleaks. In the aortic arch and at the thoracoabdominal transition, landing zone length is usually limited by the offspring of the major aortic side-branches. Exact deployment of the stent-graft to effectively use the whole length of the landing zone and to prevent occlusion of one of the side-branches is key to successful TEVAR. There are numerous techniques described to lower blood pressure and to reduce or eliminate aortic impulse to facilitate exact deployment of stent-grafts including pharmacologic blood pressure lowering, adenosine-induced asystole, inflow occlusion, and rapid pacing. Aim of this review was to assess the current literature to identify which of the techniques is best suited to prevent displacement and allow for precise placement of the stent-graft and safe balloon-molding.
Keywords: review; TEVAR; stent-graft; rapid pacing; induced hypotension; inflow occlusion; adenosine